Semi-rational engineering of CYP153A35 to enhance ω-hydroxylation activity toward palmitic acid - Jung, Eunok; Park, Beom Gi; Yoo, Hee Wang; Kim, Joonwon; Choi, Kwon Young; Kim, Byung Gee (Applied Microbiology and Biotechnology, 2018)
CYP153A35 from Gordonia alkanivorans was recently characterized as fatty acid ω-hydroxylase. To enhance the catalytic activity of CYP153A35 toward palmitic acid, site-directed saturation mutagenesis was attempted using a semi-rational approach that combined structure-based computational analysis and subsequent saturation mutagenesis. Using colorimetric high-throughput screening (HTS) method based on O-demethylation activity of P450, CYP153A35 D131S and D131F mutants were selected. The best mutant, D131S, having a single mutation on BC-loop, showed 13- and 17-fold improvement in total turnover number (TTN) and catalytic efficiency (kcat/KM) toward palmitic acid compared to wild-type, respectively. However, in whole-cell reaction, D131S mutant showed only 50% improvement in ω-hydroxylated palmitic acid yield compared to the wild type. Docking simulation studies explained that the effect of D131S mutation on the catalytic activity would be mainly caused by the binding pose of fatty acids in the substrate access tunnel of the enzyme. This effect of D131S mutation on the catalytic activity is synergistic with that of the mutations in the active site previously reported.
Keywords: Catalytic efficiencies; Computational analysis; CYP153; Cytochrome p450; Fatty acid omega-hydroxylase; High-throughput screening; Rational design; Saturation mutagenesis; Catalysis; Catalytic Domain; Colorimetry; Cytochrome P-450 Enzyme System; Gordonia Bacterium; High-Throughput Screening Assays; Hydroxylation; Kinetics; Molecular Docking Simulation; Mutagenesis, Site-Directed; Mutation; Palmitic Acid; Protein Engineering; Substrate Specificity; CYP153; Cytochrome P450; Rational design; ω-hydroxy palmitic acid